2012
DOI: 10.1038/nature11446
|View full text |Cite
|
Sign up to set email alerts
|

A magnified young galaxy from about 500 million years after the Big Bang

Abstract: The early Universe at redshift z∼6-11 marks the reionization of the intergalactic medium, following the formation of the first generation of stars. However, those young galaxies at a cosmic age of < ∼ 500 million years (Myr, at z > ∼ 10) remain largely unexplored as they are at or beyond the sensitivity limits of current large telescopes. Gravitational lensing by galaxy clusters enables the detection of high-redshift galaxies that are fainter than what otherwise could be found in the deepest images of the sky.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
347
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(372 citation statements)
references
References 38 publications
24
347
1
Order By: Relevance
“…et al 2015; orange squares, CANDELS/GOODS/HUDF, Oesch et al 2014; blue triangles, CLASH cluster searches, Zheng et al 2012, Coe et al 2013. The empty blue square shows the integrated star formation rate from Atek et al (2015) at z = 7, which is consistent with all of our models.…”
Section: Predictions For High-redshift Galaxy Observationssupporting
confidence: 83%
“…et al 2015; orange squares, CANDELS/GOODS/HUDF, Oesch et al 2014; blue triangles, CLASH cluster searches, Zheng et al 2012, Coe et al 2013. The empty blue square shows the integrated star formation rate from Atek et al (2015) at z = 7, which is consistent with all of our models.…”
Section: Predictions For High-redshift Galaxy Observationssupporting
confidence: 83%
“…e Instruments we used for spectroscopy: D = DEIMOS, M = MOSFIRE, G = HST grism from the GLASS program (Schmidt et al 2014;Treu et al 2015). f First reported by Zheng et al (2012). g Also reported by Bradley et al (2014).…”
Section: Macs 0454mentioning
confidence: 93%
“…This procedure has been shown to be very effective in locating multiple images in many clusters (e.g., Zitrin et al , 2012bZitrin et al , 2013Zitrin et al , 2015, even without any multiple images initially used as input (Zitrin et al 2012a). Most of the multiple images in MACSJ1149.5+2223 that were found by Zheng et al (2012) were identified with this method.…”
Section: Description Of the Inference Process And Error Estimationmentioning
confidence: 99%